Creando experiencias para la promoción del bienestar emocional mediante el diseño positivo generando autoconocimiento emocional y desarrollo personal (2024)
In the current century, emotional well-being has gained fundamental relevance in addressing underlying issues in society. This has led to a growing awareness of the importance of proper emotional management and its impact on personal development. The project focuses on creating an emotionally enriching experience through products designed for this purpose, aiming to improve emotional well-being and promote personal development